Error Probability of DPPM UWB Systems over Nakagami Fading Channels with Receive Diversity. (13th March 2011) - Zhang, Hao; Lu, Ting-ting; Wang, Jing-jing; Gulliver, T. Aaron
Abstract : We consider differential-pulse position modulation (DPPM) in an ultra wideband (UWB) communication system. A typical format for a DPPM signal in a UWB system is derived from that of a pulse position modulation (PPM) signal. The error probabilities of a UWB DPPM system with receive diversity over additive white Gaussian noise (AWGN) and Nakagami fading channels are derived. Both single-user and multiuser environments are considered. Performance results are presented which show that the frame error rate (FER) with DPPM is better than that with PPM, and the FER performance can be improved significantly by receive diversity.